PERBANDINGAN UNJUK KERJA GENERATOR SINKRON MAGNET PERMANEN FLUKS AKSIAL DENGAN VARIASI JUMLAH LILITAN STATOR - , RUDY DHARMAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study was conducted to determine the effect of the number of windings on the stator axial flux permanent magnet generator, with the goal to improve the performance of the generator. Generator which is used is an axial flux permanent magnet synchronous generator with double rotor and single stator owned by Laboratorium Teknik Tenaga Listrik TE UGM. The method has been done by modifying the stator part, changing the number of stator winding. The number of the original coil is 110. A new stator with number of windings 220 is made without increasing outside diameter of coil. Laboratory scale testing has been done. An induction motor is used as prime mover and a variable resistance as load. The results showed the voltages increased from average voltage of each phase 18.35 volt to 30.27 volt at phase R, 30.42 volt at phase S, and 30.21 volt at phase T at a frequency of 50 Hz. The maximum 3 phases power that can be tested increased to 43.75 watts at a frequency of 50 Hz. Voltage regulation showed similar results, means greater voltage drops due to drop in rotational speed happened. The results also showed larger voltage drop due to increased length of copper, but produced better efficiency curve.